A Novel Tree Shrew Model of Chronic Experimental Autoimmune Uveitis and Its Disruptive Application - Hu, Kaijiao; Lv, Longbao; Huang, Hui; Yin, Guangnian; Gao, Jie; Liu, Jianping; Yang, Yaying; Zeng, Wenxin; Chen, Yan; Zhang, Ni; Zhang, Feiyan; Ma, Yuhua; et al. (Frontiers in Immunology, 2022)
Background: Previous studies have established several animal models for experimental autoimmune uveitis (EAU) in rodents without the fovea centralis in the human retina. This study aimed to develop and disrupt the application of a novel EAU model in tree shrews with a cone-dominated retina resembling the human fovea. Methods: Tree shrews were clinically and pathologically evaluated for the development and characteristics of EAU immunized with six inter-photoreceptor retinoid-binding proteins (IRBPs). IRBP-specific T-cell proliferation and serum cytokine of tree shrews were evaluated to determine the immune responses. Differentially expressed genes (DEGs) were identified in the eyes of tree shrews with EAU by RNA-sequencing. The disruptive effects of the DEG RGS4 inhibitor CCG 203769 and dihydroartemisinin on the EAU were investigated to evaluate the potential application of tree shrew EAU. Results: IRBP1197–1211 and R14 successfully induced chronic EAU with subretinal deposits and retinal damage in the tree shrews. The immunological characteristics presented the predominant infiltration of microglia/macrophages, dendritic cells, and CD4-T-cells into the uvea and retina and pathogenic T helper (Th) 1 and Th17 responses. The subretinal deposits positively expressed amyloid β-protein (Aβ), CD8, and P2Y purinoceptor 12 (P2RY12). The crucial DEGs in R14-induced EAU, such as P2RY2 and adenylate cyclase 4 (ADCY4), were enriched for several pathways, including inflammatory mediator regulation of transient receptor potential (TRP) channels. The upregulated RGS4 in IRBP-induced EAU was associated with mitogen-activated protein kinase (MAPK) activity. RGS4 inhibition and dihydroartemisinin could significantly alleviate the retinal pathological injuries of IRBP1197-1211-induced EAU by decreasing the expression of CD4 T-cells. Conclusion: Our study provides a novel chronic EAU in tree shrews elicited by bovine R14 and tree shrew IRBP1197-1211 characterized by retinal degeneration, retinal damage with subretinal Aβ deposits and microglia/macrophage infiltration, and T-cell response, probably by altering important pathways and genes related to bacterial invasion, inflammatory pain, microglial phagocytosis, and lipid and glucose metabolism. The findings advance the knowledge of the pathogenesis and therapeutics of the fovea-involved visual disturbance in human uveitis.